2017
DOI: 10.1016/j.jare.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid and acute kidney injury: A mini review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 108 publications
1
84
1
2
Order By: Relevance
“…Serum creatinine is a measure of the glomerular filtration rate and is used as an index of renal function in clinical practice [37]. Hyperuricemia has also been acknowledged as an independent predictor for kidney injury [38,39]. Contrary to our expectations, none of the 2 renal biochemical markers were altered significantly in the farmers when compared to the reference group, suggesting integrity of the kidneys in farmers.…”
Section: Supplementary Materialscontrasting
confidence: 64%
“…Serum creatinine is a measure of the glomerular filtration rate and is used as an index of renal function in clinical practice [37]. Hyperuricemia has also been acknowledged as an independent predictor for kidney injury [38,39]. Contrary to our expectations, none of the 2 renal biochemical markers were altered significantly in the farmers when compared to the reference group, suggesting integrity of the kidneys in farmers.…”
Section: Supplementary Materialscontrasting
confidence: 64%
“…High levels of urinary UA (uUA) can cause kidney damage, which may be acute – for example, through stone formation (nephrolithiasis) or intrarenal obstruction (acute urate nephropathy) – or chronic, as in chronic (or gouty) nephropathy. Acute kidney injury can occur when UA concentrations in renal tubules reach supersaturation, which also depends on urine pH . Chronic nephropathy is thought to result from long‐term hyperuricosuria, in which UA concentrations may be below supersaturation.…”
Section: Introductionmentioning
confidence: 99%
“…High serum uric acid concentrations may induce endothelial dysfunction by decreasing NO bioavailability, stimulating vascular smooth muscle cell proliferation and activating the renin-angiotensin system, which cumulatively lead to microvascular damage and dysfunction. 14,15 Higher levels of serum uric acid in a population of asymptomatic subjects were independently associated with endothelial dysfunction. 27 Moreover, in two prospective studies of healthy Chinese and Korean men high uric acid levels were found to be associated with development of retinal arteriolar narrowing 22 and microalbuminuria, 28 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…11 Recently, uric acid has been a key area of focus as a potential causal factor in a multitude of diseases including but not limited to hypertension, nephropathy, atherosclerosis, heart failure and acute kidney injury. [12][13][14][15][16][17][18] The common pathophysiologic denominator of these pathways is thought to be oxidative stress and inflammation resulting from a hyperuricemic state. 19 In vitro studies demonstrated that the pro-oxidative and pro-inflammatory state induced by hyperuricemia leads to microvascular dysfunction through stimulation of vascular smooth muscle cell proliferation, inhibition of endothelial cell function and activation of renin-angiotensin system.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%